EVALUASI KUALITAS WEBSITE PEMESANAN RAMEN 1 TRANSMART PEKALONGAN MENGGUNAKAN METODE MCCALL - Khofifah, Nurul; Fiyyah, Luth; Afiani, Marshela; Janah, Fitrotul; Miranti, Putri (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2025)
The rapid advancement of Industry 4.0 underscores the need to integrate internet technology into everyday societal functions, including the food service industry. This research evaluates the quality of a web-based ordering system for Ramen 1 restaurant at Transmart Pekalongan using the McCall software quality model to assess the alignment between system capabilities and user expectations. Data were collected from 30 respondents, including both users and staff, selected based on their direct experience with the system. Assessment focused on five key quality attributes: correctness, reliability, usability, efficiency, and integrity. The results demonstrate high performance in correctness (95%), yet reveal significant shortcomings in reliability (17.09%) and efficiency (27.4%), suggesting issues related to system stability, cross-platform functionality, and backend integration. Usability and security improvements are also recommended to enhance user satisfaction and data protection. This study provides deeper insights into gaps between user needs and system performance within the McCall framework. The findings contribute to a broader understanding of how structured quality evaluation can guide strategic improvements in web-based applications, particularly within the restaurant and service sectors, to better meet user demands and technological standards. Â